Curves of AW(k)-type in 4D Galilean Space - Kulahci, Mihriban (Amer Inst Physics, 2016)
In this paper, we investigate curves of AW(k)-type (1 <= k <= 3) in 4D Galilean space and we give curvature conditions of these kind of curves. Also, we study weak AW(2)-type curves. Furthermore, we express mannheim curves of AW(k)-type in 4D Galilean space.
International Conference on Advances in Natural and Applied Sciences (ICANAS) -- APR 21-23, 2016 -- Antalya, TURKEY
Keywords: Harmonic Curvatures; Null Curves